A composite indicator for measuring the environmental performance of water, wastewater, and solid waste utilities. (February 2022) - Mergoni, Anna; D'Inverno, Giovanna; Carosi, Laura
Abstract: The aim of this paper is to measure and benchmark the environmental performance of Portuguese utilities jointly active in the three sectors of water supply, wastewater collection and solid waste management. To do so, we suggest the use of a traditional (optimistic) directional distance Benefit of the Doubt index. We complement the analysis by considering also the pessimistic version of the proposed BoD and by implementing a robust and conditional approach. The obtained results show that there is space for improvement in the pressure balance of these utilities, especially for small and very large units, mostly operating in urban areas. Highlights: An environmental pressure indicator for water and waste utilities is proposed. The composite indicator accounts for positive/negative pressures on the environment. A robust and conditional directional distance Benefit of the Doubt index is used. The environmental pressure of Portuguese water and waste utilities is evaluated. The tool is useful from a policy perspective and results are analyzed accordingly.